Attracting foreign capital: wartime case - GAIDUTSKYI, Андрій (Ius Modernum, 2023)
The decrease in the pace of development of the world economy due to the pandemic and high inflation significantly affected the volume of foreign capital attraction in developing countries. A full-scale war in Ukraine in 2022-2023 further reduced the attractiveness of their economies for foreign investors. In this regard, the purpose of the article is to study the prerequisites and mechanisms for increasing Ukraine’s investment attractiveness during hostilities. To achieve the goal, the methodological and analytical approaches for processing the databases of UNCTAD and FDI Intelligence, NBU, State Statistics Service, research by other authors regarding the geographical, labour, resource, economic and logistics potential of the economy of Ukraine were used in the article. It was found that even before the war, the country attracted significantly more investments than others from the group of countries with a lower than average income. At the same time, it is emphasized that if we want to significantly increase the inflow of capital, we need to stimulate the inflow of savings of Ukrainian migrants and the diaspora, the volume of which has been stable over the past 10 years (unlike direct investment). The prerequisites for increasing the investment attractiveness of the economy are geographical location, natural resources, developed agriculture, an agreement on association and free trade with the EU, the status of a candidate for EU membership, qualified and inexpensive labour force, etc. And the best mechanisms for increasing investment attractiveness during the war are the experience of Israel, which managed to build a financial infrastructure of investment insurance, as well as compensation for direct and indirect losses to investors who suffered from hostilities in the country during shelling or enemy attacks. Also, a number of international organizations are ready to implement foreign investment insurance projects in the country. Ukraine has every opportunity to use this experience to start attracting larger amounts of capital from all types of investors of foreign or Ukrainian origin